Methodological levels of research the post-industrial development of the city - Olha Suptelo (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
Since the middle of the twentieth century, most countries of the world are in a phase of significant socio-economic transfor-mations. The main vector of these transformations is the transition to the post-industrial stage of development, which was predicted by a number of scientists from many industries at the turn of the nineteenth and twentieth centuries. There is a logical relationship between the level and stage of development of the country. So the highly developed countries of the world are already in the phase of post-industrial development. For countries with a low level of development and a powerful and complex industrial past, such as the post-Soviet and post-socialist countries of Eastern Europe, the transition to post-industrial development, the so-called post-industrial transformations, is characteristic. A detailed study of these processes makes it possible to predict the possible paths of developed countries and individual territories. The city, as the main agent for transforming the territory, plays a major role in the country's transition to the post-industrial level of development. This article is devoted to the methodological features of studying the features of post-industrial urban development. In contemporary human geography, there is an active discourse on the issue of methodological support for research, which mainly focuses on the feasibility of applying qualitative and quantitative methods and the possibilities of their interdisciplinary application. However, in our opinion, the more complex the object of study, the wider and more directional should be the methodological apparatus of research. In this case, one should take into account the territorial aspect of this study and select methods solely for their effectiveness in achieving their goals. The author proposes to classify research methods of the features of the post-industrial development of the city according to hierarchical levels of influence of the city: global, regional and local levels. Also, this paper offers a generalized algorithm of socio-geographical study of features of post-industrial urban development, which presents the main stages of the study and proposes the most common methods of study.